2018
DOI: 10.21873/cgp.20114
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Proteome Analysis of Peripheral Blood Mononuclear Cells (PBMCs) to Identify Candidate Biomarkers of Pancreatic Cancer

Abstract: Background/Aim: Pancreatic cancer (PC) is currently the fourth leading cause of cancer-related mortality worldwide. Peripheral blood mononuclear cells (PBMCs) is a subpopulation of accessible and functional immune cells. Comparative analysis of the proteome of PBMCs can help us elucidate the mechanism of disease and find potential biomarkers for diagnosis. Materials and Methods: PBMCs were collected from healthy individuals, patients with benign diseases, and pancreatic cancer. iTRAQ-2DLC-MS/MS and SWATH metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Given that MPS IVA is a dynamic entity that involves alterations in the expression of multiple proteins, proteomics techniques can provide important biological information that can help advance our understanding of the underlying pathophysiological mechanisms. Moreover, proteomics could aid the identification of novel disease biomarkers [ 28 , 30 , 31 ], which can facilitate disease diagnosis, prognosis, and monitoring [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that MPS IVA is a dynamic entity that involves alterations in the expression of multiple proteins, proteomics techniques can provide important biological information that can help advance our understanding of the underlying pathophysiological mechanisms. Moreover, proteomics could aid the identification of novel disease biomarkers [ 28 , 30 , 31 ], which can facilitate disease diagnosis, prognosis, and monitoring [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, proteomics provides important biological information that contributes to the advance in our understanding of pathophysiological mechanisms and aid in the identification of novel biomarkers for different diseases [30,32,33]. Specific biomarkers identified from proteomics may be useful in diagnosis, prognosis, and as evaluators of treatment outcomes [34,35,36,37,38,39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…However, the commonly used biomarkers, including AFP, have significant diagnostic limitations and novel biomarkers identified from patient blood samples would be valuable in screening for HCC. Furthermore, previous studies have suggested that analyzing the genetic changes in PBMCs may be a valid method for identifying novel biomarkers ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) are immune cells that include lymphocytes and monocytes, and play a key role in the host immune system to fight against various abnormal conditions such as infection and carcinoma ( 6 ). Various studies have demonstrated that the gene expression level of PBMCs was significantly changed in patients with tumors and detection of changes in PBMCs may help to improve the diagnosis ( 7 , 8 ). Ciarloni et al ( 9 ) demonstrated the potential for developing a noninvasive and accurate inspection to identify patients at an average risk of colorectal cancer based on gene expression analysis of PBMCs segregated from patient blood samples.…”
Section: Introductionmentioning
confidence: 99%